2022
DOI: 10.1002/acp.3994
|View full text |Cite
|
Sign up to set email alerts
|

Learning by explaining after pauses in video lectures: Are provided visuals a scaffold or a crutch?

Abstract: Explaining after pauses in a video lecture can be an effective learning activity, yet students need support to generate comprehensive explanations. This study tested whether providing students access to the visualizations from the video enhances explanation comprehensiveness and transfer performance. Undergraduates (n = 112) watched a 5-part lesson on the human kidney consisting of explanations and drawings.After each part, students typed an explanation without access to information from the video (explain gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Separate from our predictions, we found that students who taught with provided visuals or words engaged in greater knowledge building than students who taught with generated visuals or words, though this did not translate into better performance on the post‐tests. This pattern is aligned with recent work showing that explaining from provided representations may at times serve as a crutch (e.g., Fiorella, 2022), supporting higher quality explanation performance during learning but not supporting better learning outcomes. Provided representations may make it easier to generate inferences when the representations are available, but learners may not internalize this knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…Separate from our predictions, we found that students who taught with provided visuals or words engaged in greater knowledge building than students who taught with generated visuals or words, though this did not translate into better performance on the post‐tests. This pattern is aligned with recent work showing that explaining from provided representations may at times serve as a crutch (e.g., Fiorella, 2022), supporting higher quality explanation performance during learning but not supporting better learning outcomes. Provided representations may make it easier to generate inferences when the representations are available, but learners may not internalize this knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…An alternative approach is asking students to make judgments about their ability to engage in effective sensemaking tasks, or generative learning activities (Fiorella & Mayer, 2016, 2022. For example, students may be prompted to rate how well they can explain the learning material to themselves or to a friend.…”
Section: Types Of Jols: Test Performance Explaining and Drawingmentioning
confidence: 99%
“…First, the findings suggest that instructors cannot assume students will productively make use of visualizations for assessing their own level of comprehension. Students may not engage in the generative processing necessary for internalizing a visual representation and integrating it with their own mental model (Fiorella, 2022;Fiorella et al, 2021). Future research should consider interventions aimed at increasing attention to and engagement with instructional visualizations like combining drawing tasks and provided visualizations.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…However, empirical findings are yet to converge on the effect of generating drawings to support explanations. For instance, studies by Fiorella and Kuhlmann (2020) and Fiorella (2022a) found that drawing can support the instructional explanation compared to using the sole strategy (Fiorella, 2022a; Fiorella & Kuhlmann, 2020). Specifically, Fiorella and Kuhlmann (2020) found that when undergraduates studied a lesson about the human respiratory system, generating drawings enhanced instructional explanation compared to only drawing or instructional explanation.…”
Section: Introductionmentioning
confidence: 99%